Foraging Behavior Shows Individual-Consistency Over Time, and Predicts Range Use in Slow-Growing Free-Range Male Broiler Chickens - Ferreira, Vitor Hugo Bessa; Simoni, Arthur; Germain, Karine; Leterrier, Christine; Lansade, Léa; Collin, Anne; Mignon-Grasteau, Sandrine; Le Bihan-Duval, Elisabeth; Guettier, Elodie; Leruste, Hélène; Løvlie, Hanne; Calandreau, Ludovic; et al. (Frontiers in Veterinary Science, 2022)
Recent research on free-range chickens shows that individual behavioral differences may link to range use. However, most of these studies explored individual behavioral differences only at one time point or during a short time window, assessed differences when animals were out of their social group and home environment (barn and range), and in specific tests or situations. Therefore, it is yet unclear how different behaviors relate to range use and how consistent these behaviors are at the individual level. To fill this gap, we here aimed to describe the behavioral budget of slow-growing male broiler chickens (S757N) when in their social group and home environment during the whole rearing period (from the second week of life to the twelfth week, before slaughter), and to relate observed behavioral differences to range use. For this, we followed a sample of individuals in two flocks (n = 60 focal chickens out of 200 chickens per flock), over two seasons, during three periods: before range access (from 14 to 25 days old), during early range access (first weeks of range access, from 37 to 53 days old), and during late range access (last weeks of range access, from 63 to 87 days old). By the end of each period, individual tests of exploration and social motivation were also performed, measuring exploration/activity and sociability propensities. Our results show that foraging (i.e., pecking and scratching at the ground) was the only behavior that correlated to range use for all three time periods, independent of the season. Foraging was also the only behavior that showed within-individual consistency from an early age and across the three time periods. Foraging may, therefore, serve as a useful behavioral predictor of range use in free-range broiler chickens. Our study increases the knowledge of how behaviors develop and relate to each other in a domesticated and intensely selected species, and improves our understanding of the biology of free-range broiler chickens. These findings can, ultimately, serve as a foundation to increase range use and improve chicken welfare.